PENGARUH PENAMBAHAN AIR BELIMBING WULUH (Averrhoa bilimbi) SEBAGAI PENGGANTI ASAM ASETAT GLASIAL TERHADAP KUALITAS NATA DE PAPAYA - Tika, Pujaan; Widowati, Hening; Zen, Suharno (Universitas Muhammadiyah Metro, 2022)
The broken and priceless of papaya in the market potentially modified as Nata called nata de papaya with the help of Acetobacter xylinum. During the fermentation, acid condition were needed by bacteria to growth and developement. Acetid acid glasial 99,8% were needed to make acid condition. The use of Averrhoa bilimbi as the subtitutan of glacial acetid acid were predicted can reduce the effect of chemical substance in food. The aim of this study to 1) know the effect of adding averrhoa bilimbi water toward the quality of nata de papaya, and 2) determined the exactly level of the averrhoa bilimbi extract toward the quality of nata de papaya. This research use Complitely Randomized Design (CRD) using 3 treatment of adding averrhoa bilimbi extract (2 ml, 5 ml, 8 ml) and 6 replicant. The data were collected by the observation by using measurement tools and organoleptic test by presenting 10 panelis. Data were analized by using Kruskal Wallis Analisis. Based on the result, could be known that there is no relation of treatment by adding averhoa bilimbi toward quality of nata de papaya. which is shown that averhoa bilimbi could subtitute the role of glacial acetid acid in the process of making nata de papaya.